HUBUNGAN LAMA SAKIT DENGAN MANIFESTASI KLINIS PADA PASIEN CUTANEOUS LUPUS ERYTHEMATOSUS DI KOMUNITAS LAMPUNG TAHUN 2019 - Vini Nugraheni; Resati Nando Panonsih; Ratna Purwaningrum; Toni Prasetia (Universitas Fort De Kock, 2020)
Cutaneous Lupus Erythematosus (CLE) is a chronic disease of the skin that may require a long-term care and follow-up. Erythema, burning, scaling, itching, scarring, dyspigmentation, as well as the pain and the length of one of these diseases can be divided into acute and chronic.To the purpose of this research was to determine the correlatiom between long sick with clinical manifestasions in Cutaneous Lupus Erythematosus (CLE) patients in Lampung year 2020. This type of research is peneltian observational analytic with cross sectional approach. Samples of this research that people with lupus in Lampung as many as 45 people. Data were obtained through a questionnaire to fill a long illness and a physical examination. Data analysis techniques to test the hypothesis that the Chi-square test. The research showed a correlation between long sick with clinical manifestasions in Cutaneous Lupus Erythematosus (CLE) in Lampung Year 2019. Given between long sick with clinical manifestasions in Cutaneous Lupus Erythematosus (CLE) that the statistical test results obtained with p-value 0.000 (less than ɑ 0,05) which means Ha accepted.